Les Défis Economiques Fondateurs de la Nouvelle Afrique du Sud - Maurice, Pierre (Victoria University of Wellington Law Review, 2004)
The basic economic challenge that faces a new South Africa has recently been recognised and made evident by official statistics. This article considers that challenge first by looking at poverty in the Republic, second by considering the resources that are available to address poverty, and finally by suggesting measures that can be used to direct the wealth of the nation to meeting the most pressing needs.